Optimalisasi Hasil Belajar Peserta Didik Melalui Pembelajaran Covid-19 Tema Pekerjaan di Kelas B1 Tk Negeri Percontohan Kota Payakumbuh Semester Genap Tahun Pelajaran 2020/2021 - Destri Warni; Jummiati Jummiati; Isti Komariyah (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study aims to see and analyze the improvement of student Learning Outcomes through Covid 19 Learning on the theme of work in Class B1 of the Pilot State Kindergarten of Payakumbuh City Even Semester TP 2020/2021, This research was conducted using the Classroom Action Research method which consists of two cycles, where each cycle consists of planning, action, reflection, and evaluation. It was carried out from January to March 2021. The data is processed in each cycle and then analyzed using percentages. The results obtained from this study are able to improve student learning outcomes. This is evidenced by the increase in student learning outcomes in the field of motoric development for 5 activity points. In the implementation of the pre-cycle the learning outcomes of students ranged from 30% to 50%, cycle I began to increase ranging from 50%, to 60% and in the implementation of cycle II the learning outcomes of students have experienced a better increase, ranging from 70% to 80% with the value category Developing As Expected (BSH). The conclusion obtained from this research is that through Covid Learning 19 Offline Methods can improve student learning outcomes. Keywords: Covid 19 learning, student learning outcomes, offline methods.